Human Rights Views on Suspects' Legal Efforts to Obtain Examination Minutes - Irvan Abdillah (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
Human rights are an important aspect of law enforcement as intended by the International Covenant on Civil and Political Rights ratified by the UN which also applies in Indonesia. This provision was then adopted into the Criminal Procedure Code (KUHAP), especially in Article 72 which gives the suspect and his legal counsel the right to obtain a copy of the examination report which is important for defendants. Through a normative legal research method with a legal and contextual approach, this study analyzes Article 72 from the perspective of civil and political rights. The results showed that the absence of clear consequences for investigators who do not comply can weaken the suspect's rights in legal defense. Therefore, it is necessary to strengthen legal provisions so that investigators are required to provide this important document, to ensure transparency and justice in future law enforcement.